GAMBARAN HEMATOKRIT PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT UMUM DAERAH ARIFIN AHMAD PROVINSI RIAU - Novasiska Indriyani Hutajulu; Amsar A Taudjidi; Fridayenti " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTHematocrit is one of the risk factors of stroke. Elevated hematocrit will cause the increased of blood viscosity. This increased of blooad viscosity will lead to activation of the substance of blooad coagulation and the derivation of cerebral blood flow. This research was to know the profile of hematocrit in ischemic stroke patients in Neurology Department Arifin Ahmad General Hospital of Riau Province during January-December 2013. This was a descriptive retrospective study. Data is used about 89 medical record of ischemic stroke patients. Data obtained from this study that the most ischemic stroke patients were in the age group 50-59 years old (32,58%), with the highest gender was male, which as much 46 patients (51,69%), the number of elevated hematocrit in male were 7 patients (7,87%) and 15 patients in female (16,86%), the number of normal hematocrit in male were 37 patients (41,57%) and in female 24 patients (26,97%), the number of lowered hematocrit in male were 2 patients (2,24%) and 4 patients (4,49%) in female. The result of this study showed that most of the ischemic stroke patients in General Hospital of Riau Province have normal hematocrit.Key words : Stroke, Ischemic stroke, hematocrit